COVID-19 Testing and the Impact of the Pandemic on the Miami Adult Studies on HIV Cohort. (1st August 2021) - Tamargo, Javier A.; Martin, Haley R.; Diaz-Martinez, Janet; Trepka, Mary Jo; Delgado-Enciso, Ivan; Johnson, Angelique; Mandler, Raul N.; Siminski, Suzanne; Gorbach, Pamina M.; Baum, Marianna K.
Abstract : Background: Socioeconomic disadvantages and potential immunocompromise raise particular concerns for people living with HIV (PLWH) and other marginalized communities during the COVID-19 pandemic. In this study, we explored COVID-19 testing and the impact of the pandemic among participants from the Miami Adult Studies on HIV cohort, predominantly composed of low-income minorities living with and without HIV. Methods: Between July and August 2020, a telephone survey was administered to 299 Miami Adult Studies on HIV participants to assess COVID-19 testing, prevention behaviors, and psychosocial stressors. Health care utilization, antiretroviral adherence, food insecurity, and substance use during the pandemic were compared with those of their last cohort visit (7.8 ± 2.9 months earlier). Results: Half of surveyed participants had been tested for COVID-19, 8 had tested positive and 2 had been hospitalized. PLWH (n = 183) were 42% times less likely than HIV-uninfected participants to have been tested. However, after adjustment for age, employment, COVID-19 symptoms, mental health care, and substance use, the effect of HIV status was no longer significant. PLWH were more likely to have seen a health care provider, use face coverings, and avoid public transportation and less likely to be food insecure and drink hazardously. There were significant changes in substance use patterns during the pandemic when compared with those before. Conclusion: PLWH, compared with their HIV-uninfected peers, were more likely to engage in preventive measures and health care during the pandemic, potentially reducing their exposure to COVID-19. There were no reported changes in antiretroviral adherence or health care utilization, but there were changes in substance use; these need to be monitored as this crisis progresses.